Does exercise training change physical activity in people with COPD? A systematic review and meta-analysis - Ng, L.; Mackney, J.; Jenkins, Susan; Hill, Kylie (Arnold, 2012)
A systematic review and meta-analysis was conducted to examine the effect of exercise training on daily physical activity (PA) in people with chronic obstructive pulmonary disease (COPD). MEDLINE, PubMed, EMBASE, CINAHL, Physiotherapy Evidence Database (PEDro) and Cochrane Central Register of Controlled Trials were searched from their inception to week 27 of 2010, using the keywords ‘COPD,’ ‘exercise,’ ‘therapy’ and ‘physical activity.’ All studies except case reports were eligible for inclusion provided they investigated the effects of ≥4 weeks of supervised exercise training on PA in patients with COPD. Study quality for the randomised trials (RTs) and single-group interventional studies was rated using the PEDro scale and Downs and Black Tool, respectively. No randomised controlled trials met our study criteria. The two RTs had a mean PEDro score of 5. The 5 single-group studies had a mean Downs and Black score of 19 ± 3. When combined, a small effect on PA outcomes was demonstrated (overall mean effect = 0.12; p = 0.01). Taken together, the RTs and single-group studies demonstrate that exercise training may confer a significant but small increase in PA.